2018
DOI: 10.1111/jce.13779
|View full text |Cite
|
Sign up to set email alerts
|

Is adenosine useful for the identification of atrial fibrillation triggers?

Abstract: Introduction: Both isoproterenol (Iso) and adenosine (Ado) are used to induce atrial fibrillation (AF) in the electrophysiology lab. However, the utility of Ado has not been systematically established.Objective: The purpose of this study was to compare Ado to Iso for the induction of paroxysmal AF.Methods: Forty patients (16 women; mean age, 60 ± 12 years) with paroxysmal AF, presenting for ablation were prospectively included of whom 36 (90%) received Ado (18-36 mg) and/or Iso (3-20 µg/min incremental dose) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…It is reported that adenosine induces AF triggers especially from RA and SVC, but the clinical significance of these foci is questionable [24,25]. On the other hand, ISPinduced AF is more likely initiated from the PVs as compared to that after the administration of adenosine [24]. We also found that all adenosine-induced AF was from RA and SVC.…”
Section: Arrhythmogenic Focisupporting
confidence: 57%
See 1 more Smart Citation
“…It is reported that adenosine induces AF triggers especially from RA and SVC, but the clinical significance of these foci is questionable [24,25]. On the other hand, ISPinduced AF is more likely initiated from the PVs as compared to that after the administration of adenosine [24]. We also found that all adenosine-induced AF was from RA and SVC.…”
Section: Arrhythmogenic Focisupporting
confidence: 57%
“…Some reports have confirmed the effects of adenosine and ISP on the search for arrhythmogenic foci. It is reported that adenosine induces AF triggers especially from RA and SVC, but the clinical significance of these foci is questionable [ 24 , 25 ]. On the other hand, ISP-induced AF is more likely initiated from the PVs as compared to that after the administration of adenosine [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that when isoproterenol and adenosine were administered to the same patients, isoproterenol mainly induced a PV trigger, whereas adenosine-induced a non-PV trigger, especially in RA. However, the trigger site induced by isoproterenol was correlated with recurrence, whereas the non-PV trigger induced by adenosine did not show a clear correlation with recurrence [ 18 ]. In addition, isoproterenol is more useful than adenosine when non-PV triggers are induced with isoproterenol and adenosine [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients are much more likely to be free of AF after ablative treatment if AF is paroxysmal. The success rate is around 60% for paroxysmal AF while it is 40% for persistent AF after a three year follow-up [21]. Recurrence rates are also significantly higher for persistent AF after an initially successful treatment.…”
Section: Introductionmentioning
confidence: 94%